Analysis of Libles Obscuur in Civil Suits in Medan State Court - Danial Syah (International Journal of Science, Technology & Management, 2021)
The research study about first to find out the reasons for the judge declaring a lawsuit unclear or obscure (obscuur libel) and second is to find out the consequences of an unclear or obscure lawsuit (obscuur libel). In this study using qualitative data analysis. The approach method in this research is to use a normative juridical approach, namely an approach that is carried out by collecting secondary data.The results of this study were (1) The reason the judge stated that a lawsuit was unclear or obscure (obscuur libel) were nine factors that caused the claim submitted by the plaintiff to be unacceptable. The nine factors are: (a) The identity of the parties (Plaintiff and Defendant). (b) The object of the lawsuit being litigated is unclear. (c) Petitum lawsuit exceeds the claim posita. (d) Power of attorney does not meet the requirements. (e) The lawsuit is filed by an underage / incapable person. (f) Claims are not filed on time. (g) Incomplete parties. (h) The court is not competent to hear the claim that is submitted. (i) The grounds of the plaintiff's rights are not clear. (2) As a result of a lawsuit is unclear or obscure (obscuur libel), then the person concerned does not accept such a decision, because the decision does not give satisfaction to what he wants from the claim as stated in the lawsuit. Because the verdict cannot be accepted in practice in the District Court based on the consideration that the plaintiff's claim is unacceptable, in fact it is a consideration regarding the subject matter of the case, namely whether the plaintiff is the owner or entitled to the suspect land, it is more appropriate to declare the claim rejected. Therefore, the plaintiff's unclear rights to the object of the lawsuit in dispute are not appropriate to be used as legal considerations to declare the claim unacceptable.